Evolution of CuO thin films through thermal oxidation of Cu films prepared by physical vapour deposition techniques. (1st June 2023) - Mahana, Debashrita; Mauraya, Amit Kumar; Singh, Preetam; Muthusamy, Senthil Kumar
Abstract: Understanding the conversion process of Cu thin films into copper oxide via thermal oxidation reaction is critical to determine their environmental stability as well as to prepare copper oxide thin films and nanostructures. This study reports the evolution of copper oxides through the thermal oxidation of Cu metal thin films deposited using two different processes i.e., DC sputtering and vacuum evaporation. The sputtered Cu films contain a fine-granular morphology with some porosity while the evaporated Cu films have a compact, coarse-granular surface. The oxidation of deposited Cu films was performed in ambient air at different temperatures ranging from 200 to 400 °C for 2–5 h. The polycrystalline cubic phase of Cu completely converts into a polycrystalline, cubic phase of Cu2 O at 300 °C and the complete conversion of Cu2 O phase into thermally stable, single-phase monoclinic CuO is achieved at 400 °C. The Cu2 O and CuO films having a crystallite size of ∼15 nm exhibit an optical band gap of ∼2.3 and ∼1.8 eV, respectively. It is found that the CuO phase evolves through Cu2 O intermediate phase via solid-state-reaction between Cu and oxygen. It is further noticed that the sputtered Cu films with smaller grains oxidize faster than the evaporated films having large-sized grains. Highlights: DC sputtered and evaporated Cu films are oxidized at different temperatures. Initial granularity of Cu thin films critically determines their oxidation rate. Complete conversion of Cu2 O and CuO phases occurs at 300 and 400 °C, respectively. DC sputtered Cu films with smaller grains oxidize faster than evaporated films.